Pharmacological Effect of Micellized and Conventional Vitamin D3 on Letrozole-Induced Polycystic Ovary Syndrome in Female Rats - Dahak, Bushra Mohammed Hussein Ahmed (University of Science and Technology, Sana’a, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by hormonal imbalances, metabolic disturbances, and reproductive dysfunction. Hypovitaminosis D is prevalent among PCOS patients and may exacerbate associated metabolic abnormalities. This study aimed to study the pharmacological effect of micellized vitamin D3 (MVD3) and conventional vitamin D3 (CVD3) on letrozole (LTZ)-induced PCOS in rats, evaluating their impact on hormonal balance, metabolic markers, lipid profiles and ovarian histology. Thirty female Albino rats were randomly divided into five groups: a control group (1 ml of 1% carboxymethylcellulose orally), a PCOS group: (LTZ 200μg/d), a metformin-treated group: (LTZ, 200μg/day alongside with 155 mg/kg of metformin), a CVD3-treated group: (LTZ, 200μg/day along with 1000 IU/kg of CVD3) and a MVD3-treated group: (LTZ, 200μg/day along with 1000 IU/kg of MVD3). Treatments were administered daily by oral route for 90 days. Estrous cycle evaluation was conducted via vaginal cytology. Across all groups, body and ovarian weights, body mass index, serum levels of 25(OH) vitamin D, fasting plasma glucose, fasting serum insulin, insulin resistance, lipid profile parameters, Luteinizing hormone, Follicle-stimulating hormone, testosterone, estradiol, progesterone were measured. Ovaries were dissected for histopathological examination. This study showed that LTZ-induced PCOS group showed a statistically significant increase in body mass index and the serum levels of insulin, glucose and calculated homeostatic model assessment of insulin resistance (HOMA-IR), cholesterol, triglycerides, low density lipoprotein, testosterone, follicle stimulating hormone and luteinizing hormone levels . In contrast, there was a statistically significant decrease in the serum levels of vitamin D, high density lipoprotein (HDL), estradiol and progesterone levels. Interestingly, all of these measures were improved with MVD3 and CVD3 supplementation in the treated group as well as with metformin treatment. MVD3 demonstrating greater efficacy in reducing testosterone and elevating HDL-c. Furthermore, both MVD3 and CVD3 supplementation reduced the number of the cystic ovarian follicles observed in the histopathological examination. This study provides strong evidence that MVD3 and CVD3 can effectively alleviate PCOS-related metabolic, hormonal disturbances, and morphological disturbances, with MVD3 demonstrating superior therapeutic benefits. These findings suggest that MVD3 may serves as a promising intervention for PCOS management.
Keywords: Vitamin D3; Letrozole; Polycystic Ovary Syndrome (PCOS); Pharmacology; Sana'a; Yemen